Photobiomodulation Therapy as a Treatment for Patients with Lip Paresthesia Due to Inferior Alveolar Nerve Trauma during Dental Procedures: Report of Three Cases - narjes hoshyari; Nazgol Zamanian; Fatemeh Doost Mohammad (Mashhad University of Medical Sciences, 2023)
Background: Iatrogenic damage to the inferior alveolar nerve (IAN) is one of the possible complications that may occur during dental procedures. In this study, we examined three patients who suffered from IAN damage and lip paresthesia after receiving dental care and were then treated with photobiomodulation (PBM) therapy.Case Report: Case 1; a 56-year-old woman presenting with lip, chin and buccal mucosa paresthesia following the extraction of the left mandibular second molar and bone grafting. The patient admitted to our clinic after 18 months with the diagnosis of IAN related paresthesia and was treated with PBM therapy. Case 2; a 38-year-old woman reported sensory loss in lip, chin and buccal mucosa in the right quadrant after implant placement.  Implant was removed immediately and after two weeks, patient underwent PBM treatment which was performed in two cycles that were 6 months apart. Case 3; A 29-year-old woman suffered from lip, chin and buccal mucosa paresthesia in the right site after receiving a single-visit mandibular molar root canal treatment. She underwent PBM therapy after two weeks. Diode 980 nm laser was used. Treatment outcomes were assessed by measuring the palpation and thermal sensation of the affected area using visual analogue scale (VAS). The obtained VAS scores were compared with those of the intact side of the mandible. All three patients reported that sensation in the numbed area improved during the treatment sessions and complete or partial recovery was achieved after the treatment period.Conclusion:  Since PBM therapy is able to stimulate the regeneration of the damaged IAN, it can be considered as a non-invasive treatment option with minimal complications.